Coordinated MFAILC of Multiple High-Speed Trains Subject to False Data Injection Attacks - Wei, Y.; Junjie, M.; Huang, Deqing (Data Driven Control and Learning Systems Conference (Online), 2024)
This study presents a coordinated model free adaptive iterative learning controller (MFAILC) for multiple high-speed trains (MHSTs) subjected to random false data injection attacks (FDIA). Firstly, the nonlinear train system is converted as a linear one that solely relies on input and output (I/O) information of the trains. Subsequently, by establishing an attack model using random variables, the coordinated MFAILC is developed. Furthermore, the convergence analysis is conducted based on mathematical expectation, followed by numerical simulation to verify the validity of the control scheme.